2022
DOI: 10.1002/hbm.26126
|View full text |Cite
|
Sign up to set email alerts
|

An artificial‐intelligence‐based age‐specific template construction framework for brain structural analysis using magnetic resonance images

Abstract: It is an essential task to construct brain templates and analyze their anatomical structures in neurological and cognitive science. Generally, templates constructed from magnetic resonance imaging (MRI) of a group of subjects can provide a standard reference space for analyzing the structural and functional characteristics of the group. With recent development of artificial intelligence (AI) techniques, it is desirable to explore AI registration methods for quantifying age‐specific brain variations and tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…To emphasize, this segmentation process depends on VB-Net, achieving efficient, precise, and end-to-end segmentation of multiple sub-regions. The model was trained on T1 images of 1,800 subjects and tested on 295 subjects with an average Dice of 0.92, where the images were acquired from the Consortium for Reliability and Reproducibility (CoRR) dataset ( 65 ) and Chinese brain molecular and functional mapping (CBMFM) project ( 66 ). Based on the segmentation results, the volume, volume ratio of each sub-region, and the asymmetry index of paired sub-region are calculated quantitatively and compared to the relevant parameters from the gender- and age-matched normal dataset ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…To emphasize, this segmentation process depends on VB-Net, achieving efficient, precise, and end-to-end segmentation of multiple sub-regions. The model was trained on T1 images of 1,800 subjects and tested on 295 subjects with an average Dice of 0.92, where the images were acquired from the Consortium for Reliability and Reproducibility (CoRR) dataset ( 65 ) and Chinese brain molecular and functional mapping (CBMFM) project ( 66 ). Based on the segmentation results, the volume, volume ratio of each sub-region, and the asymmetry index of paired sub-region are calculated quantitatively and compared to the relevant parameters from the gender- and age-matched normal dataset ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, MRI techniques were successfully used to diagnose lung cancer, liver cancer, prostate, and breast cancer cells, and AI was also integrated into these techniques, allowing them to be integrated into multidisciplinary applications allowing patient-specific medicine to be personalized [ 137 , 138 , 139 ]. This investigation clearly demonstrated that AI should be integrated into designing the magnetic materials for MRI imaging and the obtained MRI images successfully enhance the diagnostic capabilities [ 140 ].…”
Section: Cancer Diagnosismentioning
confidence: 99%
“…It is worth noting that research has found that as the degree of artificial intelligence anthropomorphism increases, the moral responsibility attributed to it also increases, and this effect is achieved through the enhancement of artificial intelligence’s perceived free will caused by anthropomorphism. 33 Therefore, although a higher level of anthropomorphism can lead to algorithm appreciation, excessive anthropomorphism can also result in algorithm aversion and even generate the “uncanny valley effect” (the feeling of unease when AI becomes too intelligent, leading to a decrease in preference). 34 …”
Section: Psychological Mechanisms Of Algorithm Aversion and Appreciat...mentioning
confidence: 99%